Pearlitic ductile cast iron: damaging micromechanisms at crack tip - F. Iacoviello; V. Di Cocco; A. Rossi; M. Cavallini (Fracture and Structural Integrity)
Ductile cast irons (DCIs) are characterized by a wide range of mechanical properties, mainly depending on microstructural factors, as matrix microstructure (characterized by phases volume fraction, grains size and grain distribution), graphite nodules (characterized by size, shape, density and distribution) and defects presence (e.g., porosity, inclusions, etc.). Versatility and higher performances at lower cost if compared to steels with analogous performances are the main DCIs advantages. In the last years, the role played by graphite nodules was deeply investigated by means of tensile and fatigue tests, performing scanning electron microscope (SEM) observations of specimens lateral surfaces during the tests (“in situ” tests) and identifying different damaging micromechanisms. In this work, a pearlitic DCIs fatigue resistance is investigated considering both fatigue crack propagation (by means of Compact Type specimens and according to ASTM E399 standard) and overload effects, focusing the interaction between the crack and the investigated DCI microstructure (pearlitic matrix and graphite nodules). On the basis of experimental results, and considering loading conditions and damaging micromechanisms, the applicability of ASTM E399 standard on the characterization of fatigue crack propagation resistance in ferritic DCIs is critically analyzed, mainly focusing the stress intensity factor amplitude role.